Regulatory T cell expansion prevents retinal degeneration in type 2 diabetes - María Llorián-Salvador; Daniel Pérez-Martínez; Miao Tang; Anna Duarri; Marta García-Ramirez; Anna Deàs-Just; Anna Álvarez-Guaita; Lorena Ramos-Pérez; Patricia Bogdanov; Jose A. Gomez-Sanchez; Alan W. Stitt; Cristina Hernández; et al. (Journal of Neuroinflammation)
Abstract Background The global incidence of type 2 diabetes (T2D) is rapidly increasing, with retinopathy being its most common complication and a leading cause of preventable blindness. Although the precise mechanisms involved in the development of diabetic retinopathy (DR) are not fully understood, defective immunomodulation is a recognized key factor in its pathophysiology. Regulatory T cells (Treg) regulate inflammation and promote regeneration, and while they are known to have important anti-inflammatory and neuroprotective roles in other tissues, including central nervous system, their role in the diabetic retina remains largely unknown. The aim of the present study is to examine the effect of Treg expansion of retinal neurodegeneration, an early event in the pathogenesis of DR. Methods Treg expansion was achieved by co-injecting recombinant mouse IL-2 with anti-IL-2 monoclonal antibody or its isotype in db/db mice as an established model of T2D. Treg expansion was confirmed via flow cytometry in blood, spleen, and retina. Fundus angiography was performed in the days prior to animal sacrifice at 18 weeks. To study the effect of Tregs on retinal neurons, glia and vascular permeability, immunohistochemistry against Cone-Arrestin, PKCα, synaptophysin, ChAT, TH, GFAP, Iba-1, calbindin, Brn3a, RBPMS, isolectin B4, and albumin was used. Retinal VEGF levels were measured with a magnetic bead-based immunoassay, and NLRP3, Casp1, p20 and IL-18 were analyzed by Western Blot in retinal homogenates. Results There was a significant decrease in Treg in db/db mice blood. When this deficiency was corrected in db/db mice by systemic Treg expansion, there was an effective protection against retinal neurodegenerative, gliotic, inflammatory changes and vascular leakage associated with T2D. Importantly, Treg expansion did not impact the T2D phenotype in db/db mice as evaluated by blood glucose, HbA1c and circulating insulin. Conclusion Treg modulation in T2D offers a promising therapeutic approach to prevent early stages of DR. This strategy focuses on reducing neuroinflammation and mitigating the associated neuronal, glial, and vascular degenerative changes characteristic of DR.